Non-equilibrium plasma enhanced oxygen vacancies of CuO/CeO2 nanorod catalysts for toluene oxidation. Issue 3 (June 2022) - Yun, Jianyu; Wu, Liangkai; Hao, Qinglan; Teng, Zihao; Gao, Xin; Dou, Baojuan; Bin, Feng
Abstract: The development of non-noble metal catalyst is essential for VOCs controlling. Cu-Ce based catalyst is a promising catalyst, and the oxygen vacancies dominants the catalytic oxidation process but the traditional calcination is not conducive to its generation. Herein a series of CuO/CeO2 nanorod catalysts for toluene oxidation were prepared with non-equilibrium plasma comparing with traditional calcination. It is found that the treatment of non-equilibrium plasma after calcination can significantly enhance the synergism between CuO active phase and CeO2 support leading to high dispersion of CuO. And the non-equilibrium plasma is favorable to increase Cu + /Cu 2+ and Ce 3+ /Ce 4+ ratios generating more oxygen vacancies in the catalyst. In the process of toluene oxidation, the rich oxygen vacancy can accelerate adsorption and activation of gaseous oxygen which consequently improve the catalytic activity for toluene oxidation. Graphical Abstract: ga1 Highlights: Oxygen vacancy (Ov ) in Cu-Ce catalyst dominants VOCs oxidation. Traditional calcination is not conducive to Ov generation. Non-equilibrium plasma (NEP) was used to prepare CuO/CeO2 . NEP treatment after calcination enhances synergy between CuO and CeO2 . Enhanced synergy improves Ov and gaseous oxygen activation for activity.